Extent Of Social Media Engagement and Academic Performance of Senior High School Students in Kayapa East District - Mallo, Aiza (International Journal of Sustainability and Advanced Integrated Research, 2026)
Social media platforms such as Facebook, TikTok, YouTube, Instagram, and Discord have become integral to students’ daily lives. This study explored the extent of social media engagement and its relationship with the academic performance of Senior High School students in Kayapa East District during the School Year 2025–2026. This study employed a quantitative descriptive-correlational research design. The respondents comprised 198 ABM Senior High School students selected through complete enumeration sampling. Data were collected using a structured and validated questionnaire that focused on respondents’ profiles, the effects of social networking sites on learners’ lives, academic performance, and challenges encountered in using social media. Frequency, percentage, weighted mean, standard deviation, and Pearson Product-Moment Correlation Coefficient were used to analyze the data. The findings indicated that Facebook was the most commonly used social networking site, while Android cellphones were the primary devices used by respondents. Social networking sites positively influenced learners’ mental, social, physical, spiritual, and emotional aspects, with the mental aspect receiving the highest rating. Social media engagement also has positive effects on academic performance and learning engagement when used responsibly and for educational purposes. However, students also face challenges such as distraction, excessive use, and poor time management. Correlation analysis revealed a moderately significant positive relationship between social media engagement and academic performance. The study concluded that responsible and balanced use of social media may support students’ engagement and academic success while minimizing its negative effects on their mental health.
Keywords: Academic Performance; Learning Engagement; Senior High School Students; Social Networking Sites; Social Media Engagement